Sintesis Magnesium Ferit Berbasis Pasir Besi dari Sarmi menggunakan Metode Kopresipitasi - Cahyo Saputra; Heru Cahyoutomo; Jeny Sendong; Octolia Togibasa (Jurnal Fisika FLUX, 2020)
In this study, magnesium ferrite was sinthesized from natural iron sand using co-precipitation method. Iron sand material was taken from the north coast of Sarmi Regency, Papua Province. The purpose of this study was to find out whether magnesium ferrite could be synthesized from iron sand directly without preliminary processes into magnetite minerals. Co-precipitation method was applied with a variant of stirring temperature of 30, 50 and 70°C. The crystal structures was characterized using an x-ray diffractometer, while the magnetic properties was characterized using a vibrating sample magnetometer and the morphology of the particle was characterized using a scanning electron microscpe. From the results of characterization, it is known that magnesium ferrite successfully synthesized from iron sand directly without preliminary processes into magnetite minerals. Magnetic properties were obtained from the sample with added of magnesium acetate tetrahedral and stirred at a temperature of 70°C. The x-ray diffracttion pattern showed figure of merit of 0.82, while the magnetic hysterisis curve shows coercivity of 200 Oe and magnetic moment about 11 emu/gr. The mineral has irregular particle sizes that range from 0.5 to 100 microns in size, due to magnetic attraction which promotes agglomeration. This researcher recommends optimization of the synthesis process so that the quality of the magnesium ferrite can be improve.